2020
DOI: 10.1186/s43045-020-00047-8
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic and demographic factors associated with adaptive behaviour among children diagnosed with autism spectrum disorder in Egypt

Abstract: Background Adaptive behaviour among children diagnosed with autism spectrum disorder determines wide range of self-independent and autonomous activities. Adaptive behaviour is a clearly defined measurable variable that can be used as an outcome, hence impacts intervention and training programs. The current study aims to determine the socio-economic and demographic factors that are associated with adaptive behaviour among children diagnosed with autism spectrum disorder in Egypt. In this observational cross sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This is due to better parental awareness and education as well as better access to medical services among the higher SES as confirmed by many other studies. Similar results attributed this finding to either a lack of knowledge among families with lower SES or to patients in the high socioeconomic group having ASDs that were more severe and required earlier medical treatment (30) .…”
Section: Discussionmentioning
confidence: 60%
“…This is due to better parental awareness and education as well as better access to medical services among the higher SES as confirmed by many other studies. Similar results attributed this finding to either a lack of knowledge among families with lower SES or to patients in the high socioeconomic group having ASDs that were more severe and required earlier medical treatment (30) .…”
Section: Discussionmentioning
confidence: 60%
“…In another study of socio economic and demographic factors associated with adaptive behavior in Egypt, Ibrahim et al, (2020) found that the adaptive behaviour functions among the children diagnosed with autism disorder difference significantly according to age in all domains. They used Vinland Adaptive behavioural scale to assess the informants' adaptive level.…”
Section: Introductionmentioning
confidence: 96%
“…As a result, this contributes to the unmet needs of pupils with ASD in Egypt, which could have a dramatic impact on the child ‫الرتبوية‬ ‫العلوم‬ ‫يف‬ ‫للبحوث‬ ‫الدولية‬ ‫ملجلة‬ ‫ا‬ and family's well-being (Gobrial 2018;Taha & Hussein 2014). Further challenges include scarce knowledge of ASD, scarcity of professionals, barriers to diagnosis and treatment, limited resources for ASD and lack access to intervention services (Ibrahim et al 2020;Gobrial, McAnelly & Shannon 2019;Ghoneim 2014;Gobrial 2012;Jenkins, Heshmat, Loza, Siekkonen & Sorour 2010).…”
Section: Introductionmentioning
confidence: 99%